Effectiveness of Neuraminidase Inhibitors for Prevention of Influenza - Deonandan, Raywat; Mensinkai, Shaila; Hodgson, Amanda (Université d'Ottawa | University of Ottawa, 2007)
In a given influenza season, affected individuals exhibit symptoms that are laboratory-confirmed influenza (LCI) or influenza-like illness (ILI). A subset of patients who have ILI are truly infected with the influenza virus, because the same symptoms may result from other seasonal pathogens. LCI and ILI are characterized by respiratory discomfort, fatigue, aches, headache, and fever. While yearly vaccine formulations are generally well tolerated for seasonal influenza, in a pandemic setting, it is unlikely that a vaccine would be available immediately. Thus, antiviral agents may be a viable option for preventing influenza. This report investigates the evidence about the use of two neuraminidase inhibitors (NIs), zanamivir (Relenza TM) and oseltamivir (Tamiflu TM), for the prophylaxis of influenza. Oseltamivir is available as a tablet and powder for oral suspension, and zanamivir is administered through a diskhaler inhalation device.